2022
DOI: 10.1038/s41398-022-02063-0
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type specific changes in PKC-delta neurons of the central amygdala during alcohol withdrawal

Abstract: The central amygdala (CeA) contains a diverse population of cells, including multiple subtypes of GABAergic neurons, along with glia and epithelial cells. Specific CeA cell types have been shown to affect alcohol consumption in animal models of dependence and may be involved in negative affect during alcohol withdrawal. We used single-nuclei RNA sequencing to determine cell-type specificity of differential gene expression in the CeA induced by alcohol withdrawal. Cells within the CeA were classified using unbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 67 publications
2
13
0
Order By: Relevance
“…This uncovered many new CEA cell types, their participation in CEA circuitry, and revealed their relationships to previously identified CEA marker genes. Recently, single-nucleus RNA sequencing from the CEA in rat identified 13 neuronal types (11/13 neuronal types were from CEA) ( Dilly et al, 2022 ). We found good correspondence with major CEA cell types identified by Dilly et al, such as the Prkcd and the Crh neurons in the CeC and CeL, and the Drd1 and Drd2 neurons in the CeM.…”
Section: Discussionmentioning
confidence: 99%
“…This uncovered many new CEA cell types, their participation in CEA circuitry, and revealed their relationships to previously identified CEA marker genes. Recently, single-nucleus RNA sequencing from the CEA in rat identified 13 neuronal types (11/13 neuronal types were from CEA) ( Dilly et al, 2022 ). We found good correspondence with major CEA cell types identified by Dilly et al, such as the Prkcd and the Crh neurons in the CeC and CeL, and the Drd1 and Drd2 neurons in the CeM.…”
Section: Discussionmentioning
confidence: 99%
“…In the CeL, we found two clusters marked by expression of Sst: the CeL Sst cluster which contains the largest and most highly expressing population of Sst-positive neurons, and the CeL NTS/Tac2 cluster which contains low expressing Sst-positive cells. This is consistent with previous observations (Kim et al ., 2017; McCullough et al ., 2018) and a recent single cell transcriptomics study in the rat CeA (Dilly et al, 2022). Optogenetic manipulation of these two clusters separately suggested that both drive appetitive behavior (Kim et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This transcriptome signature is less common in mammals (e.g., refs. 59 , 68 , 69 ). We did not detect other neuron types in this brain region.…”
Section: Resultsmentioning
confidence: 99%